Relationship between intermuscular adipose tissue infiltration and myostatin before and after aerobic exercise training - Konopka, Adam R.; Wolff, Christopher A.; Suer, Miranda K.; Harber, Matthew P. (American journal of physiology. Regulatory, integrative and comparative physiology, 2018)
Intermuscular adipose tissue (IMAT) is associated with impaired skeletal muscle contractile and metabolic function. Myostatin and downstream signaling proteins such as cyclin-dependent kinase 2 (CDK2) contribute to the regulation of adipose and skeletal muscle mass in cell culture and animals models, but this relationship remains incompletely understood in humans. The purpose of this study was to determine if the infiltration of IMAT was associated with skeletal muscle myostatin and downstream proteins before and after 12 wk of aerobic exercise training (AET) in healthy older women (OW; 69 ± 2 yr), older men (OM; 74 ± 3 yr), and young men (YM; 20 ± 1 yr). We found that the infiltration of IMAT was correlated with myostatin and phosphorylated CDK2 at tyrosine 15 [P-CDK2(Tyr15)]. IMAT infiltration was greater in the older subjects and was associated with lower skeletal muscle function and exercise capacity. After 12 wk of AET, there was no change in body weight. Myostatin and P-CDK2(Tyr15) were both decreased after AET, and the reduction in myostatin was associated with decreased IMAT infiltration. The decrease in myostatin and IMAT occurred concomitantly with increased exercise capacity, skeletal muscle size, and function after AET. These findings demonstrate that the reduction in IMAT infiltration after AET in weight stable individuals was accompanied by improvements in skeletal muscle function and exercise capacity. Moreover, the association between myostatin and IMAT was present in the untrained state and in response to exercise training, strengthening the potential regulatory role of myostatin on IMAT.